The Correlation of State and Religion from Ali Abdur Raziq's Perspective - Mohammad Nasih Al Hashas; Alfina Infitahul Mawaddah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study examines Ali Abdur Raziq's perspective on the relationship between religion and state and the background, context, and dynamics present amid the emergence of ideas from this perspective. It is a literature study that critically analyzes Ali Abdur Raziq's ideas in his book Al-Islam wa Ushul al-Hukm. This study uses a descriptive qualitative method. Islam, as a religion, rahmatan lil alamin, means a universal and comprehensive religion. Islam is here to provide solutions for all processes of human life on earth, including the belief that Islam also offers the concept of a religious and pious government system. In contrast to Ali Abdur Raziq's perspective, this Islamic figure has a secular ideology, as shown by his controversial work, Al-Islam wa Ushul al-Hukm. In his book, Raziq initiates the concept of secularization of Islam. Raziq wants to change the original Islamic religion into a secular religion like Christianity, which does not teach a government system. He believes that Islam is the only religion that conveys divine messages to people through the intermediary of the Prophet Muhammad without interfering in the slightest in political affairs and the government system. He used religious postulates with subjective interpretations. By some secular Islamic figures, Raziq is considered the founding father of modern state theology, who has saved Islam from negative political experiences that occurred throughout Islamic history. Although in the end, this idea did not get much fresh air from the majority of Islamic scholars (and was even firmly rejected), this dialectic needs to be answered with a more objective idea of realizing Islam as a universal and comprehensive religion.